The Film Balampah As A Cultural Text: A John Fiske Semiotic Analysis - Mardiana; Muzahid Akbar Hayat; Katharina Siswi Widyawati (UNIVERSITAS PAKUAN, 2026)
The film Balampah (2023, directed by Aditya Nugraha) presents a narrative rooted in Banjar culture, especially the oral traditions, ritual imagination, moral norms, and mystical beliefs that circulate in South Kalimantan. This article examines Balampah as a cultural text by using John Fiske's semiotic framework, which reads media texts through three levels of coding: reality, representation, and ideology. The research uses a qualitative descriptive method supported by observation of film scenes, documentation, and interviews with members of the production team. The analysis shows that the film encodes cultural signs through Qur'anic recitation, musala imagery, gamelan sound, dance-house space, mantra, susuk emas, amulets, pusaka, and the narrative of marwah. At the level of reality, these signs build the social world of a Banjar community caught between piety, entertainment, and magical desire. At the level of representation, camera movement, lighting, mise-en-scene, dialogue, horror conventions, and melodramatic characterization intensify the opposition between sacred order and worldly excess. At the level of ideology, the film articulates several cultural myths: moral binary opposition between religion and worldliness, occult consequence or tumbal, ancestral protection, spiritual redemption, female sanctity, and the ever-present evil. Balampah therefore functions not merely as local horror entertainment, but as a cultural discourse that reproduces collective anxieties, moral warnings, and negotiations of identity in contemporary Indonesian society.